Family / caregiver's perspective on chronic pain in palliative care patients - Silva, Rudval Souza da (2019)
The aim of this research was to know the perspective of the family/caregiver in facing the chronic pain of their loved one in palliative care. Data collection used the semi-structured interview and was performed in the months of January to April of 2018 with nine family/caregiver of patients in palliative care with chronic pain. For analysis, the Bardin Content Analysis Technique was used, and the results discussed based on the related literature. Four categories emerged from the analysis: 1) Feelings experienced by family/caregiver; 2) Limited use of analgesics as a therapeutic resource for pain control; 3) Lack of knowledge of non-pharmacological therapies in pain management; and 4) Communication as a therapeutic resource for pain relief. It is concluded that the pain is still underused, and this fact contributes to the increase of the suffering of the patient as well as the family/caregiver.